3D thermal-hydraulic analysis of a symmetric wavy parabolic trough absorber pipe. (15th December 2019) - Yang, S.; Ordonez, J.C.
Abstract: We analyzed a symmetric wavy parabolic trough absorber pipe using an experimentally validated 3D FEM coupled to a semi-analytical optical model. The proposed absorber design was assessed based on the first and second law efficiency as well as the performance evaluation criteria (PEC), which accounted for both heat transfer enhancement and pressure drop relative to a conventional design, as we varied the wave amplitude, periodicity length, and fluid mass flow rate. Significant improvement in the first law efficiency was observed with the proposed design, especially at high mass flow rates due to the accelerated flow across the pipe throat which in turn enhanced the mixing. The second law efficiency variation shifted from an increasing to a decreasing trend with respect to the wave amplitude as the mass flow rate increased, and the exergy destruction due to pressure drop became evident accordingly. The PEC verified the superior performance of the proposed absorber design over the traditional straight pipe as its peak value was approximately 1.25. We also determined critical wave amplitude, periodicity length, and mass flow rate below which the PEC was less than unity due to an escalated pressure drop that offset the heat transfer enhancement. Highlights: 3D thermal-hydraulic analysis of a novel symmetric wavy absorber pipe is presented. Periodicity length (λ), wave amplitude (A), and mass flow rate ( m ˙ f ) were varied. First law efficiency improved with the proposed design. Performance evaluation criteria (PEC) also verified its superior performance. We determined critical λ, A, and m ˙ f below which the straight absorber outperforms.